2021
DOI: 10.1111/aor.13910
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression profiles of circular RNAs in the rat hippocampus after deep hypothermic circulatory arrest

Abstract: Neurological dysfunction commonly occurs after cardiac surgery with deep hypothermic circulatory arrest (DHCA). The mechanisms underlying DHCA-associated brain injury remain poorly understood. This study determined the changes in expression profiles of circular RNAs (circRNAs) in the hippocampus in rats that underwent DHCA, with an attempt to explore the potential role of circRNAs in the brain injury associated with DHCA. Adult male Sprague Dawley rats were subjected to cardiopulmonary bypass with DHCA. Brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
2
3
0
Order By: Relevance
“…At present, a large number of studies have shown that circRNAs regulated ischemia-induced brain injury 15 , 26 . Our results confirmed that the expression profiles of circRNAs in rat hippocampus changed after the DHCA procedure, which was consistent with other studies 27 . However, the number of total circRNAs and dysregulated circRNAs in our results was far more than in the previous study 27 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…At present, a large number of studies have shown that circRNAs regulated ischemia-induced brain injury 15 , 26 . Our results confirmed that the expression profiles of circRNAs in rat hippocampus changed after the DHCA procedure, which was consistent with other studies 27 . However, the number of total circRNAs and dysregulated circRNAs in our results was far more than in the previous study 27 .…”
Section: Discussionsupporting
confidence: 93%
“…Our results confirmed that the expression profiles of circRNAs in rat hippocampus changed after the DHCA procedure, which was consistent with other studies 27 . However, the number of total circRNAs and dysregulated circRNAs in our results was far more than in the previous study 27 . Many reasons attribute to this difference, such as the differences in sequencing methods and experimental environments.…”
Section: Discussionsupporting
confidence: 93%
“…A study in fetal lambs demonstrated that WIN 55, 212-2 reduces hypoxia/ischemia-induced apoptotic cell death in the brain through the maintenance of mitochondrial integrity and functionality [ 41 ]. In our previous study, we observed ultrastructure changes in mitochondria in the hippocampus of rats following DHCA, showing swelling, cavitation of the mitochondrial matrix, and loss of the mitochondrial cristae [ 26 ]. Whether WIN 55, 212-2 preserves mitochondrial integrity and functionality to improve neuronal survival in the hippocampus is, therefore, of interest for further studies.…”
Section: Discussionmentioning
confidence: 99%
“…The CPB and DHCA procedures were performed as described in our previous study [ 26 ] with slight modifications. Briefly, after fasting for 12 h, the animals were anesthetized with 2% isoflurane.…”
Section: Methodsmentioning
confidence: 99%
“…MiR-190a, miRNA-181b-5p and miRNA-146a alleviated POCD by inhibiting hippocampal neuroinflammation ( Chen et al, 2019 ; Liu et al, 2019 ; Lu et al, 2019 ). Previous brain studies indicated that circRNAs played a unique role in the regulation of perioperative brain function through ceRNA networks ( Li et al, 2021 ). This study aimed to establish a perioperative circRNA-related ceRNA network in the hippocampus based on RNA sequencing (RNA-seq).…”
Section: Introductionmentioning
confidence: 99%